Samsung v. Apple : a struggle over patent infringement claims - Sherman, Marshall; Smith, Travis; O'Rourke, James S., 1946- (London : SAGE Publications Ltd, 2017)
On August 24, 2012, a jury in the U.S. District Court for the Northern District of California found that Samsung mobile devices infringed six Apple patents, awarding Apple $1.05 billion in damages. The lawsuit was a battle of the largest smartphone manufacturer, Samsung, and the world's largest company, Apple. Samsung must decide what actions they should take in response to the outcome reached by the jurors. Decisions at hand include trial proceedings, public communications, and research and development philosophy changes.
Originally published in Sherman, M., Smith, T., & ORourke, J. S. (2012). Samsung v. Apple: A struggle over patent infringement claims. 12-12. Notre Dame, IN: The Eugene D. Fanning Center for Business Communication, Mendoza College of Business, University of Notre Dame.
Description based on XML content.
Keywords: elektronické knihy; Samsung Telecommunications America; Apple Computer, Inc; electronic books; Patent infringement; Commercial law; Business ethics; Corporate image; Smartphones